2021
DOI: 10.1186/s43042-021-00136-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening of NKX2.5 gene in Moroccan Tetralogy of Fallot (TOF) patients: worldwide mutation rate comparisons show a significant association between R25C variant and TOF phenotype

Abstract: Background Tetralogy of Fallot is the most prevalent cyanotic congenital heart disease, occurring in 1/3 600 live births. This disorder comprises ventricular septal defect, right ventricular outflow obstruction, over-riding aorta, and right ventricular hypertrophy. The present study aims to reveal the spectrum of Nk2 homeobox 5 (NKX2-5) variants identified in a Moroccan non-syndromic tetralogy of Fallot cohort and to compare mutation rate with different studies from all over the world. Thirty-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Bioinformatic predictions indicate that the E21E variant might impair NKX2.5 transcript splicing by removing a whole exon from the transcript, resulting in translation of a shortened protein that is most likely inactive. Further in vitro functional tests are needed to validate this finding ( EL Bouchikhi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bioinformatic predictions indicate that the E21E variant might impair NKX2.5 transcript splicing by removing a whole exon from the transcript, resulting in translation of a shortened protein that is most likely inactive. Further in vitro functional tests are needed to validate this finding ( EL Bouchikhi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have also reported that variants in NKX2.5 cause a wide range of CHDs, including ASD, VSD, TOF, HLH, CoA, TGA, Double Outlet Right Ventricle (DORV), IAA, and cardiac outflow tract (OFT) anomalies; reviewed in ( Chung and Rajakumar, 2016 ). Recently, new NKX2.5 variants were discovered in a Moroccan cohort with non-syndromic TOF; a missense variant R25C and a synonymous variant E21E ( EL Bouchikhi et al, 2021 ). The R25C variant is expected to impair NKX2.5 dimerisation and impede activation of downstream target genes ( Kasahara et al, 2000 ; Dentice et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…The human NKX2-5 gene maps to chromosome 5q34 and consists of two exons that encode a 324-amino acid protein [ 16 ]. Previous studies evaluated the exonic regions of the NKX2-5 gene; however, recent findings instead investigate the mutations and associated CHDs in the intronic and promoter regions of the NKX2-5 gene [ 17 ]. Functional analysis has elucidated the mechanism of action in various mutations of the NKX2-5 gene and future studies are required in order to understand the involvement of NKX2-5 in complex cardiac abnormalities [ 18 ].…”
Section: Introductionmentioning
confidence: 99%